Porto-sinusoidal vascular liver disease in systemic sclerosis: case study - Gavrilyuk, O.M.; Havrylyuk , I.M.; Bezpalok , M.P. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. When detecting vascular lesions of the liver, especially if they are not accompanied by clear clinical symptoms, pathologists may encounter difficulties in describing and interpreting pathological manifestations due to insufficient study of this pathology and conflicting terminology. Objective. The purpose of the work is to describe a rare variant of porto-sinusoidal vascular liver disease in a patient with systemic sclerosis. Methods. Pathomorphological examination of liver and lung tissue (necropsy) using histological methods. Results. A 44-year-old patient with a confirmed (clinically and pathomorphologically) diagnosis of "systemic sclerosis" died due to respiratory failure. At autopsy, in addition to signs characteristic of systemic sclerosis (diffuse pneumofibrosis of nonspecific interstitial pneumonia type and pleuropulmonary fibroelastosis). changes in the vascular bed of the lungs and liver were detected. The latter can be attributed to several morphological patterns: complete obliteration of medium-sized vessels with replacement by concentric laminar structures, formation of hypervascularized areas of loose extracellular matrix with thin-walled vessels in the place of preexisting vessels, thickening of vessel walls due to hyperplasia and/or sclerosis with lumen stenosis. For such lesions of the hepatic vessels, a relatively new term is suitable - porto-sinusoidal vascular disease of the liver, which does not imply the presence of clinical signs of portal hypertension, which was observed in our case. The genesis of vasculopathy remains unclear, but probably an important role is played by disturbed cell-matrix (endothelial, myofibroblast) interactions characteristic of systemic sclerosis. Conclusion. Despite the rarity of porto-sinusoidal vascular disease of the liver, in each case of detection of vascular changes during the examination of liver tissue, it is necessary to conduct a thorough clinical and anatomical analysis, taking into account the scientific data available today, since this can be important both for assessing the prognosis of the disease and for selection of adequate therapy.